P‐1.2: Self‐Diver‐ Intelligent‐Pixel Architectures in In‐Ga‐Zn‐O Technology for Special‐Shaped Panel. (24th February 2021) - Shu, Yang; Wang, Mingxin; Wang, Zhijun; Zhou, Liufei; Xu, Shangjun; Wang, Lizhong; Wang, Huaipei; Fei, Mi; Bian, Cunjian; Yuan, Ling
Abstract : With the wide application of liquid crystal display (LCD), people have higher and higher requirements on various screen shapes. Especially in the field of Automotive display. However, the irregular LCD displays on the market still have limitations in shape. Not only is the display often uneven, but the border is also wide because of driver circuitry outside the Active area. Therefore, we proposed a "Self‐Driven Intelligent Pixel (SDIP)" architecture, which can independently complete the scan driver without additional configuration of GOA circuit or gate IC, and it can arbitrarily splice these pixel units to obtain any display area. Based on the SDIP technology, this paper designs a 5.9‐inch circular LCD display with a frame of 4.8mm. It provides a new design direction for arbitrary LCD screen and ultra‐narrow border technology.